Implementation of Student Character Education in Elementary Schools - Irman Matje; Muhammad Yusnan (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
This study aims to describe the implementation of character education in public elementary schools and to develop a model for character strengthening based on local culture. Using a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation involving teachers, school principals, and parents. The results indicate that character education in elementary schools has not been systematically integrated into the curriculum and learning activities. Teachers have not fully assumed the role of value facilitators, and parental involvement remains limited. The rich local culture of Buton, which embodies moral values such as kabanti, kaghati, and gotong royong, has not been explicitly utilized as a resource for character learning. This study proposes a model of character education based on local culture, comprising five main components: an integrated curriculum, teacher role modeling, contextual learning, school–parent partnerships, and character evaluation based on local values. These findings are expected to provide a practical contribution to the development of contextual, sustainable character education that is deeply rooted in regional cultural identity.